PSYCHOLOGICAL AND PEDAGOGICAL PRINCIPLES OF HIGHER EDUCATION MODELING SYSTEM IN UKRAINE IN ITS CONDITIONS OF PARADIGMATIC CRISIS - Luzik, Elvira; Kokarieva, Anzhelika (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article is devoted to a thorough scientific and theoretical analysis of the domestic and foreign scientists works concerning the construction of the psychological foundations of the higher education system modeling in the information and educational environment of higher technical education institutions of Ukraine. Aim of study was to conceptualize and operationalize the psychological and pedagogical foundations of the higher education system modeling of higher technical education institutions under the paradigmatic crisis conditions. Objectives of the study is focused on the definition of theoretical approaches to the study of the modeling problem of the higher technical education system in the information and educational environment of the Ukrainian higher technical education institutions in the conditions of its paradigmatic crisis and diversification of higher professional education; determination of the system-forming principle of the psychological and pedagogical foundations of the modeling of the higher education system within the framework of the humanistic paradigm, which ensure the forecast and achievement of the effectiveness of the functioning of the system in the projection of the goals of all interested participants of the educational process in the HTEI. There were used next research methods for the goal achieving: scientific analysis; systematization; generalization, pedagogical and mathematical modeling with using factor analysis. Results. In the course of the research, it was proved that the application of the higher education system modeling on psychological grounds in the situation of its reformation allows to resolve the main paradigmatic contradictions in the domestic psychological and pedagogical theory by means of interpretive schemes of higher school functioning and transformation: between the value attitudes of the higher technical education system diversification, with on the one hand, and the goals and means of its implementation - on the other. Conclusions. It has been identified that the communicative approach as a system of methodological tools that provide a solution to the "contradiction of the meeting" of normative and humanistic paradigms is the psychological and pedagogical basis for modeling the higher education system; interpretation of the goals (respectively, efficiency criteria or system-forming principles) of the functioning and transformation of the higher professional education (HPE) system within the framework of the humanistic paradigm, i.e. from the position of all interested participants in the educational process in the HTEI and the employment situation, which determine the limitations of the higher education system model. The system-forming principle of modeling the HPE system, determining its limitations, is the concept of competence within the framework of the humanistic approach, which is defined as a state and reflexive mechanism for achieving situational relevance and personal identity of the subject in the context of professional development.